2018
DOI: 10.1037/xhp0000440
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of a sensory prediction error signal for visuomotor adaptation.

Abstract: To accomplish effective motor control, the brain contains an internal forward model that predicts the expected sensory consequence of a motor command. When this prediction is inaccurate, a sensory prediction error is produced which adapts the forward model to make more accurate predictions of future movements. Other types of errors, such as task performance errors or reward, play less of a role in adapting a forward model. This raises the following question: What unique information is conveyed by the sensory p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 63 publications
4
28
1
Order By: Relevance
“…Task errors can drive the changes in motor commands needed to increase task success following some forms of sensorimotor perturbation (e.g. Izawa & Shadmehr, 2011;Nikooyan & Ahmed, 2015;Taylor et al, 2013), but trajectory errors seem pivotal for automatic recalibration of sensorimotor transformations (Butcher & Taylor, 2017;Izawa & Shadmehr, 2011;Shadmehr et al, 2010). Our…”
Section: Trajectory Error Processing Is Crucial For Adaptation Outcommentioning
confidence: 91%
“…Task errors can drive the changes in motor commands needed to increase task success following some forms of sensorimotor perturbation (e.g. Izawa & Shadmehr, 2011;Nikooyan & Ahmed, 2015;Taylor et al, 2013), but trajectory errors seem pivotal for automatic recalibration of sensorimotor transformations (Butcher & Taylor, 2017;Izawa & Shadmehr, 2011;Shadmehr et al, 2010). Our…”
Section: Trajectory Error Processing Is Crucial For Adaptation Outcommentioning
confidence: 91%
“…The difference between the intended movement (explicit re-aiming) and the actual reach direction reveals any learning of which the subject was unaware (implicit adaptation). These trial-by-trial assays have been extensively validated against traditional measures of implicit adaptation through direct comparison (Taylor and Ivry, 2011;Taylor et al, 2014), and convergent evidence (Poh and Taylor 2016;Butcher and Taylor 2018;Poh and Taylor 2019;McDougle and Taylor 2019). Given the advantages of disassociating explicit and implicit learning on a trial-by-trial basis, we adopted a reaiming procedure for our experiments.…”
Section: Introductionmentioning
confidence: 99%
“…An additional complication to long-term motor learning, not considered in Experiment One, is the directional nature of implicit adaptation. Several studies have revealed that the key factor to the development of implicit adaptation is the direction of the perturbation, as opposed to the size of the perturbation Thoroughman 2006, 2007;Wei and Kording, 2009;Semrau, Daitch, and Thoroughman, 2012;Morehead et al 2017;Butcher and Taylor, 2018). The implicit response to directional information appears to be automatic: the motor system automatically adapts in a direction opposite to the perturbation even when such adaptation is task-irrelevant (Schaefer, Shelly, andThoroughman, 2012, Morehead et al 2017;Butcher and Taylor, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 show results from numerical simulations demonstrating that our model generates the first seven dynamic behaviors. For all simulations the model parameters are fixed as follows: K 1 = −1/10, K 2 = 1, and G 1 = −2.…”
mentioning
confidence: 91%